Differential Effects of Natural Grazing and Feedlot Feeding on Yak Fecal Microbiota - Shah, Tariq; Ding, Luming; Ud Din, Ahmad; Hassan, Faiz-ul; Ahmad, Anum Ali; Wei, Haiyan; Wang, Xianju; Yan, Qi; Ishaq, Muhammad; Ali, Niyaz; Fang, Yougui (Frontiers in Veterinary Science, 2022)
Variation in food and diet shapes the diversity of the gut microbiota of ruminants. The present study investigated the microbial diversity in the fecal microbiota of yaks reared under natural grazing and feedlot system. A total of 48 domestic yaks with an average age of 7.5 years were selected from two different grazing habitats: one group grazed on natural pasture (grazing yaks—GY) while the other group was fed fodder and concentrate (feedlot yaks—FY). Crude protein, non-fiber carbohydrate, hemicelluloses, and digestible dry matter contents of natural pastures were higher than those in the feedlot. The lower insoluble fiber contents were found in grazing land. The 16S rRNA gene sequencing revealed 675 and 348 unique operational taxonomic units (OTUs) in the GY and FY, respectively, in addition to 1,778 common OTUs. Overall, a total of 9,891 OTUs were identified as a whole, of which 6,160 OTUs were from GY and 3,731 were from FY. Shannon index analysis revealed a higher bacterial diversity in GY than FY. At the phylum level, Firmicutes were dominant bacterial taxa in both groups. The relative abundance of Firmicutes in GY (56% ± 0.05) was higher than in FY (41% ± 0.08). At the family level, GY had a significantly higher abundance of Ruminococcaceae (p < 0.001) and Rikenellaceae (p < 0.001) than FY, but FY had a significantly higher abundance of Prevotellaceae than GY (p < 0.001). At the genus level, abundances of Faecalibacterium, Alloprevotella, and Succinivibrio were higher in FY than in GY. This study presents novel information on fecal bacterial composition and diversity in yaks reared under two different production systems.